Characteristics of osteonecrosis of the femoral head after COVID-19 steroid treatment compared to steroid-associated osteonecrosis - Takahiro Igei; Satoshi Nakasone; Mika Takaesu; Fumiyuki Washizaki; Sakura Kuniyoshi; Masamichi Onaga; Kenta Otsuki; Masato Ishihara; Chikashi Yamakawa; Kotaro Nishida (BMC Musculoskeletal Disorders)
Abstract Background Several studies have reported that the steroid dose of osteonecrosis of the femoral head (ONFH) after COVID-19 infection treatment was relatively low. However, the pathogenesis of ONFH after COVID-19 infection was not elucidated. This study aimed to analyze ONFH cases after COVID-19 infection and compare their characteristics with those of steroid-associated ONFH during the same period. Methods This study includes 8 patients diagnosed with ONFH after steroid treatment for COVID-19 infection (COVID-19 group) from January 2020 to December 2023 in our institution and associated institutions. Nine patients diagnosed as steroid-associated ONFH without COVID-19 pneumonia treatment (SA-ONFH group) during same periods. Duration of steroid administration, cumulative dose of prednisolone equivalent, time to the onset of ONFH, history of alcohol and smoking, and blood test results were analyzed. Statistical analysis was performed between both groups using Mann-Whitney U test, Fisher’s exact test (p < 0.05). Results In COVID-19 group, the mean duration of steroid administration was 31 days, the mean cumulative dose of prednisolone equivalent was 719 mg, the mean time to the onset of ONFH was 9 months, 4 patients had a history of alcohol, 5 patients had a history of smoking. In SA-ONFH group, those were 681 days, 8,720 mg, 23 months, respectively; all patients have no alcohol and smoking history. In COVID-19 group, two patients had no history of alcohol and smoking. The administration duration of steroid in COVID-19 group was significantly shorter than that of SA-ONFH group. In addition, the mean cumulative dose of prednisolone equivalent was significantly lower than that of SA-ONFH group. A systematic inflammatory response and a hypercoagulable status could not be confirmed based on blood test results. Conclusions In our results, the mean cumulative dose in COVID-19 group was 719 mg, less than the diagnostic criteria (2000 mg) and our SA-ONFH group. Even in ONFH patients without history of alcohol and smoking in COVID-19 group, steroid dose were less than the criteria. Therefore COVID-19 infection itself or low-dose of steroid for COVID-19 patients may be a contributing factor to ONFH. Patients after COVID-19 infection treated with steroids should be followed for the possibility of developing ONFH.